2013
DOI: 10.1071/an12191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the aerobic vaginal bacteria load and antimicrobial susceptibility after different oestrous synchronisation treatments in goats

Abstract: The objectives of this study were to determine (i) the variation in the bacterial population, (ii) the changes in the number of aerobic bacteria, and (iii) in vitro bacterial susceptibility to different antibiotics after the use of two different intravaginal devices (silicone devices or polyurethane sponges) for 6 or 11 days in goats. During the breeding season, 25 multiparous Saanen goats were randomly allocated to four treatments. Group IS-6 (n = 6) and Group IS-11 (n = 6) goats received a polyurethane intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
2
16
0
3
Order By: Relevance
“…In some laboratories and commercial products manufacturers recommend that to avoid vaginitis and decreases the perceived odour at sponge withdrawal, antibiotics should be added to sponges before insertion to the vagina. Although tetracycline is antibiotic, most widely used in association with sponge treatments, there are several studies reporting that it is the antibiotic with the greatest number of resistant colonies [7,9,10] and this may explain the decrease in conception rates after its application. Others observed the application of gentamycin to vaginal sponges is efficient in preventing vaginal infections provoked by intravaginal sponge [11].…”
Section: Introductionmentioning
confidence: 99%
“…In some laboratories and commercial products manufacturers recommend that to avoid vaginitis and decreases the perceived odour at sponge withdrawal, antibiotics should be added to sponges before insertion to the vagina. Although tetracycline is antibiotic, most widely used in association with sponge treatments, there are several studies reporting that it is the antibiotic with the greatest number of resistant colonies [7,9,10] and this may explain the decrease in conception rates after its application. Others observed the application of gentamycin to vaginal sponges is efficient in preventing vaginal infections provoked by intravaginal sponge [11].…”
Section: Introductionmentioning
confidence: 99%
“…The present study results showed that the use of intravaginal devices increased the bacterial number to them despite being stayed in the vagina for different durations. Manes et al (2013) stated no significant difference between devices' in vagina stay durations in terms of the number of vaginal bacteria. Al-Hamedawi et al (2003) stated some changes in the number of vaginal bacteria as a result of the physical actions exerted by the devices that retained and absorbed vaginal secretions throughout their stay in the vagina.…”
Section: Bacterial Countmentioning
confidence: 96%
“…types as the most common species in vagina of the ewes. Manes et al (2013) reported that G + bacteria as the dominant colony before insertion of the vaginal devices and Bacillus spp. as the most commonly observed species.…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…This decline in CFU/ ml arises from elimination of the irritant and also from the increase in local immunity response caused by estrogenic phase during proestrus and estrus (Martins et al, 2010). Manes et al (2013) stated that there was no significant difference between the application dates in terms of numbers of vaginal bacteria, however; that the number decreased to the levels before devices were installed on the day estrus were observed. Yeşilmen et al (2008) reported that progesterone had no significant effect on the increase in number of bacteria in vaginal flora and that the number of bacteria also increased in the ewes to which empty sponge was attached.…”
Section: Factors Leading To Change In Vaginal Microbiotamentioning
confidence: 99%
“…They recommended a drug named Ciprofloxacin for treatment of vaginitis caused by Gram positive or Gram negative bacteria. reported Cephalothin and Gentamicin type antibiotics, and Manes et al (2013) reported Amoxicillin, Ampicillin and Streptomycin as the most effective antibiotics in preventing bacterial growth. As Martin et al (2009) included in the study they made only the healthy animals which do not have antimicrobial treatment history, they expected the members of normal vaginal microflora to be rather sensitive to antibiotics that were tested.…”
Section: Data Analysesmentioning
confidence: 99%